THE MODERN PROBLEMS OF BALANCED NUTRITION IN TREATMENT AND PREVENTION OF ONCOLOGICAL DISEASES WITHIN THE SPECIAL PHARMACEUTICAL HELPING SYSTEM - Петров, Андрей Георгиевич; Хорошилова, Ольга Владимировна; Семенихин, Виктор Андреевич; Филимонов, Сергей Николаевич (Medicine in Kuzbass, 2023)
It has been found out that a well-balanced nutrition plays an important role in treating of oncological diseases. In most cases the patients consume fats, carbohydrates and calories excessively while they lack proteins, micronutrients and vitamins, which leads to progress in oncological disease.
Keywords: medical nutrition; oncological diseases